Classroom Structure and Climate Preferences Predicted by Extroversion and Introversion (Journal of Educational Sciences, 2026)
The issue of personality impact on learning preferences is as old as psychology in education. The most inevitable in this influence is certainly a dimension of temperament called extroversion-introversion. Our rigid patterns of learning behavior are determined by our physiological, emotional, and cognitive preferences, which leads to the strong assumption that our choices to learn and succeed are closely linked to the personality trait. If only teachers were aware of assets and liabilities of extrovert and introvert learners, they could provide more adaptable learning environments and help them achieve much better results. This article examines the role of extrovert and introvert personality in learning a foreign language, specifically their choices of classroom structure and climate. The research sample was 90 students of SDU University, Kazakhstan. First, Eysenck’ Personality Inventory(EPI) was implemented to measure two personality dimensions: extroversion and introversion. Then, the study compares the preferences of extroverts and introverts to competitive, cooperative, and individualized settings. Finally, we find out the associations of extroversion and introversion with three classroom climates such as innovation and building relationship, task achievement, and being under rigid control. The research reveals certain differences in learners’ classroom structure and climate preferences predicted by extroversion and introversion. Understanding the impact of personality traits in the use of classroom structure and climate for language learning is essential for designing inclusive educational environments.Key words: extroversion, introversion, learning styles, classroom structure, classroom climate.